C-Reactive Protein at Discharge, Diabetes Mellitus and ≥1 Hospitalization During Previous Year Predict Early Readmission in Patients with Acute Exacerbation of Chronic Obstructive Pulmonary Disease. (4th May 2015) - Crisafulli, Ernesto; Torres, Antoni; Huerta, Arturo; Méndez, Raúl; Guerrero, Mónica; Martinez, Raquel; Liapikou, Adamantia; Soler, Néstor; Sethi, Sanjay; Menéndez, Rosario
Abstract: Recurrent hospitalizations in acute exacerbation of chronic obstructive pulmonary disease (AECOPD) patients have clinical and economic consequences; particularly those readmitted soon after discharge. The aim of our observational study was to determine predictors of early readmission to hospital (30 days from discharge). Prospective data on 125 hospitalized AECOPD patients were collected over a 30-month period at two Spanish university hospitals. Based on readmission after discharge, patients were divided into non-readmitted ( n = 96) and readmitted (n = 29). Measures of serum inflammatory biomarkers were recorded on admission to hospital, at day 3 and at discharge; data on clinical, laboratory, microbiological and severity features were also recorded. In a multivariate model, C-reactive protein (CRP) at discharge ≥7.6 mg/L, presence of diabetes and ≥1 hospitalization for AECOPD during previous year were significant risk factors for predicting readmission. Presence of all 3 risk factors perfectly identified the readmitted patients (positive and negative predictive values of 1.000; 95% CI, 1.00–1.00). A combination of 3 readily available clinical and biochemical parameters is accurate in identifying hospitalized AECOPD patients at risk for early readmission.